Wind energy technology (WINERCOST). Issue 4 (August 2018) - Rebelo, Carlos; Correia, José; Baniotopoulos, Charalampos; De Jesus, Abílio
The special issue of the Wind Engineering journal gathers a set of invited papers presented in the International Conference on Wind Energy Harvesting that took place on 20–21 April 2017 in the University of Coimbra in Portugal and organized in the scope of the TUD COST Action TU1304 Wind energy technology reconsideration to enhance the concept of smart cities (WINERCOST). This conference and the COST action provided a forum for the presentation and discussion of different aspects of wind energy and wind energy technologies. Its principal objective was to collect the existing expertise on the Built environment Wind energy Technology (BWT) recently developed as a follow-up of the Onshore/Offshore Wind Energy Technology (ON/OFF-WET) and to investigate effective adoption methods for enabling the concept of Smart Future Cities. In addition, the utmost important issue of the social acceptance strategy will be scrutinized in close collaboration with municipality authorities, industry, manufacturers as well as the international wind energy organizations and platforms. The initiative addressed a wide variety of topics included in five themes: (1) Wind Characteristics and Loads; (2) Structures, Materials and Dynamics; (3) Grid Integration, Operations and Control; (4) Markets, Strategies, Policies; and (5) Socio-economics Smart Cities and Environmental Aspects. Also, the participation of young researchers in this action has been encouraged and pursued by giving the opportunity to the early stage researchers of the Marie-Curie Innovative Training Network AEOLUS4FUTURE to present their projects and results. The selection of papers for this special issue of the journal addressed exclusively those presented in the topic on Structures, Materials and Dynamics as well as Wind and Wave Characteristics and Loads (Baniotopoulos et al., 2017).